Improving human nutrition through agricultural research: overview and objectives - Pinstrup-Andersen, Per (United Nations University, 2000)
There has been little dialogue in the past between agricultural scientists and human nutritionists to explore ways to solve the problem of malnutrition in developing countries together. This conference, held at an agricultural research center in a developing country, provides a unique opportunity to have such a dialogue. About one-half of the 95 in attendance are trained as human nutritionists, and nearly an equal number are plant scientists.International agricultural research has made a major contribution to growth in food supplies in developing countries. It is widely recognized that lowering the prices of food staples has had a tremendously beneficial impact in alleviating malnutrition. However, the magnitude of micronutrient malnutrition as a public health concern, and the crucial role of poor dietary quality as an underlying cause, have now become widely recognized. Does agriculture have an equally important role to play in addressing micronutrient malnutrition as it has had in alleviating low energy intakes? It is at this crossroads that this conference meets.Formally, the conference has been convened as a meeting of scientists from the 16 centres that comprise the Consultative Group on International Agricultural Research (CGIAR), with the objectives of taking stock of human nutrition-related research at CGIAR centres, determining research gaps and priorities for future CGIAR research, and identifying opportunities for outside collaboration and cooperation. A three-day conference agenda is designed to accomplish these goals, while at the same time allowing a general discussion of agriculture–nutrition linkages with partners from outside the CGIAR.